2021
DOI: 10.1007/s00894-021-04833-x
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin: a blocker of SARS-CoV-2 cell entry based on relaxed complex scheme, molecular dynamics simulation, and metadynamics

Abstract: Natural products have served human life as medications for centuries. During the outbreak of COVID-19, a number of naturally derived compounds and extracts have been tested or used as potential remedies against COVID-19. Tetradenia riparia extract is one of the plant extracts that have been deployed and claimed to manage and control COVID-19 by some communities in Tanzania and other African countries. The active compounds isolated from T. riparia are known to posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Furthermore, our results revealed that CBNA could bind to Tyr453 of SARS-CoV-2 RBD-ACE2, consistent with the binding between luteolin and ACE2 [ 16 ]. This indicates that CBNA and luteolin all have the potential ability to block viral recognition and entry.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Furthermore, our results revealed that CBNA could bind to Tyr453 of SARS-CoV-2 RBD-ACE2, consistent with the binding between luteolin and ACE2 [ 16 ]. This indicates that CBNA and luteolin all have the potential ability to block viral recognition and entry.…”
Section: Resultssupporting
confidence: 68%
“…When luteolin was targeted at RdRP by molecular docking, and its docking score was −7.62 kcal/mol [ 15 ], it suggested there were differences in inhibition of SARS-CoV-2 even when the same bioactive molecule was targeted on different proteins. The binding energy of luteolin-inhibited cell entry was −36.82 kJ/mol [ 16 ], while CBDA was −6.3 kcal/mol [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hydrophobic contacts of (S)-Linezolid with ACE2 were also found to be common with those of OC, namely Asn N33 and Pro P389. Furthermore, binding contacts N33, H34, D38, Y453, and P389 (with the latter playing a critical role in the interaction of both OEU and OC on ACE2), were revealed to be in common with luteolin [ 99 , 100 ]; N33, H34, and P389 were in common with andrographolide; H34, A387, and P389 were in common with artemisinin; and H34 was in common with pterostilbene [ 26 ], bound at the same RBD/ACE2 interface.…”
Section: Resultsmentioning
confidence: 99%
“…All of the above-mentioned individual antiviral and antibiotic drugs have been tested for the prevention and effective management of COVID-19 infection. Till now the available clinical data validated that most of the repurposed drugs tested for COVID-19 treatment, have shown lower or moderate effectiveness with many adverse side effects for the patient conditions like diabetes, hypertension, cardiac problems 19 , 20 . Many repurposed combination drugs have also repositioned for the treatment of HIV, other coronaviruses and MERS-CoV infection [ 21 ].…”
Section: Introductionmentioning
confidence: 99%